Efeito da laserterapia pr??via sobre o reparo m??sculo esquel??tico de rato - Cardoso, Beatriz Guimar??es Ribeiro (2013)
The low level laser therapy (LLLT) is widely used in order to promote faster and better repair muscle with reference to different types of injury, however, studies on the prior application of the laser are scarce. The aim of this study is to evaluate the effect of LLLT prior to injury on the repair process and the matrix metalloproteinase MMP-2. For that, were used 40 Wistar rats divided into 5 groups: (G1) Control, (G2) Sham; (G3) No lesion with LLLT immediately prior to sacrifice; (G4) LLLT immediately prior to muscle injury TAD; (G5) Only injury without treatment with LLLT. The cryoinjury applications consist of two rod cooled in liquid nitrogen directly into the TA muscle. Groups 4 and 5 were assessed at 1, 3 and 7 days after injury. The LLLT were performed using the GaAlAs laser (?? 780nm) with the density energy of 10 J/cm??, output power of 40 mW, time of 10 seconds per point, with 8 points of application and total energy 3.2 J. After treatment, the TA muscles were removed and sections were obtained with the assistance of a microtome for morphology analysis using hematoxylin-eosin and collagen using Picrosirius staining. To assess the activity of MMP-2 is used technique Zymography in the different groups and its characterization technique was used for Western blotting. The results demonstrate that LBP applied prior to induction of the injury caused a reduction of inflammatory cells after 3 days, myonecrosis after 1 and 3 days, an increase of blood vessels after 3 and 7 days and after 7 days immature fibers. There was increased activity of MMP-2 after 7 days and reduced collagen deposition in the same period, with better organization of your arrangement tissue. In conclusion, LBP applied immediately before the injury induced positive effects on the modulation of inflammation and repair muscle activity of MMP-2 and organization and collagen deposition during muscle regeneration.